Emotional intelligence as a component of the physical and moral state of a leader ("Journal "U". Economy. Management. Finance.", 2020)
The purpose of the study is to disclose such a concept as emotional intelligence and to determine the importance of this concept in the working sphere of life. The article considers the influence of emotional intelligence on the physical and moral component of the employee, and how much the concept of emotional intelligence affects the productivity of the employee and the team as a whole. The article also describes the influence of emotional intelligence on leaders and their leadership abilities.
Keywords: emotional intelligence; leadership; key skills; adaptation; efficiency